2002
DOI: 10.1152/ajpgi.00323.2001
|View full text |Cite
|
Sign up to set email alerts
|

Role of TGF-β1 in the development of pancreatic fibrosis in Otsuka Long-Evans Tokushima Fatty rats

Abstract: Recently established Otsuka Long-Evans Tokushima Fatty (OLETF) rats, a model of naturally occurring obesity diabetes, exhibit progressive accumulation of connective tissue in the pancreas. The present study was designed to determine the pathogenic role of transforming growth factor-beta1 (TGF-beta1) in the development of pancreatic fibrosis in OLETF rats by investigating the serial changes in the expression of TGF-beta1 and extracellular matrix (ECM) in the pancreas. Progressive proliferation of connective tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 52 publications
2
34
0
Order By: Relevance
“…The pathogenesis of chronic pancreatitis has not been completely understood. Nevertheless, it was reported that various factors such as TGF-β1, ECM, oxidative stress etc, are involved in the progression of pancreatic fibrosis [10,11] . Since pancreatic fibrosis is the characteristic feature of chronic pancreatitis, preventing and inverting pancreatic fibrosis is the key to therapy of chronic pancreatitis and amelioration of its prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of chronic pancreatitis has not been completely understood. Nevertheless, it was reported that various factors such as TGF-β1, ECM, oxidative stress etc, are involved in the progression of pancreatic fibrosis [10,11] . Since pancreatic fibrosis is the characteristic feature of chronic pancreatitis, preventing and inverting pancreatic fibrosis is the key to therapy of chronic pancreatitis and amelioration of its prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Many studies have demonstrated the presence of TGF-b1 in the form of either protein or message, in the fibrotic tissues of human chronic pancreatitis and animal models. [8][9][10]23,32 Van Laethem et al 33 demonstrated that repeated injections of recombinant TGF-b into mice after recurrent episodes of acute pancreatitis led to pancreatic fibrosis. On the other hand, Menke et al 13 have demonstrated that inhibition of TGF-b1 by TGF-b1-neutralizing antibody causes partial reduction of the accumulation of ECM (collagen type I and III, and fibronectin) during regeneration from the cerulein-induced acute pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] Immunohistochemical staining of a-SMA was performed as described previously. 23 A DAKO EnVision system (Dako Cytomation) was used for collagen type I, fibronectin, and ssDNA immunostaining. Immunoreactivity of the Ki-67 antigen was visualized by the labeled streptavidinbiotin method (Dako Cytomation).…”
Section: Histological Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…At later than 40 weeks the rats become hypoinsulinemic, and exhibit defects in insulin secretion (9)(10)(11). Histologically, the OLETF rats also show progressive fibrosis in the pancreas (9,12). After 20 weeks, fibrosis and the enlargement of the islets clustered in connective tissue become prominent.…”
Section: Introductionmentioning
confidence: 99%